Suicide attempt and death by suicide in Brazil: an epidemiological analysis - Silva, Daniel Augusto da; Marcolan, João Fernando (Medicina (Ribeirao Preto), 2021)
Objective: Describe the epidemiological profile of suicide attempts and deaths in Brazil. Method: Retrospective, quantitative research, data obtained in September 2020 in the database of the Department of Informatics of the Brazilian Unified Health System. Results: Gradual increase in self-harm reports by 497.5% between 2011 and 2018. In 2018, from those who attemped suicide, 68.9% were women, 65.6% were aged between 20 and 59 years; and 49.4% were white. Between 2009 and 2018, there were 108,020 deaths; higher rates among males. In data from 2018, we noted similar age groups; there were important regional differences mostly among white (49.2%) and brown (42.8%); in 2017 and 2018, we noted the highest proportional percentage in people with 8 to 11 years of study: 33.1 and 35.6%, respectively. Conclusion: Increase in suicide attempt and suicide rates, according to Brazilian regions and states. Increase in the death of indigenous people; white people; men; in those single, divorced, and widowed; with more years of schooling; from all age groups; who died at home by hanging.